4(w+2)-w=2(w+1)+9

Simple and best practice solution for 4(w+2)-w=2(w+1)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(w+2)-w=2(w+1)+9 equation:



4(w+2)-w=2(w+1)+9
We move all terms to the left:
4(w+2)-w-(2(w+1)+9)=0
We add all the numbers together, and all the variables
-1w+4(w+2)-(2(w+1)+9)=0
We multiply parentheses
-1w+4w-(2(w+1)+9)+8=0
We calculate terms in parentheses: -(2(w+1)+9), so:
2(w+1)+9
We multiply parentheses
2w+2+9
We add all the numbers together, and all the variables
2w+11
Back to the equation:
-(2w+11)
We add all the numbers together, and all the variables
3w-(2w+11)+8=0
We get rid of parentheses
3w-2w-11+8=0
We add all the numbers together, and all the variables
w-3=0
We move all terms containing w to the left, all other terms to the right
w=3

See similar equations:

| -7w+3(w+2)=-2 | | 6x+14=3x+6 | | -7=5(v-2)-8v | | 9=6+b6 | | 8+2x=2(-x+7)18 | | -3(x-5=2x | | 8a-3=5a+18 | | 5(1x+7)=90 | | x=11+0.5/0.75 | | 8+5z=4z | | 9=s2+1 | | -18=-2(x+5 | | 6-5u=-4u | | -9(x+6)=-81 | | 21+0.15x=16+0.19x | | 0.3(n-5=0.4-0.2 | | 57=5y-13 | | 17/7x=136 | | 17/8x+30=16/3x | | 21/8x+30=51/3x | | 4-f=4-7f | | 7y+1=-27 | | x/(3x-5)(x+7)=0 | | 3/8(h+13)=24 | | .3n+4=7 | | 3x+38=9x=28 | | 4.4e+12=0 | | 104=m-98 | | t+12=21 | | 6x/2=2x | | 2m^2-5m=-3 | | 7w+4w=24 |

Equations solver categories